2010
DOI: 10.1002/cncr.25210
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus status in head and neck cancer

Abstract: Human papillomavirus (HPV) is an emerging causative factor for squamous carcinoma of the oropharynx and perhaps other head and neck cancers. There is a great deal of uncertainty regarding the clinical significance and implications of HPV status in this patient population. As a result, there is no established protocol for informing patients of the potential link between viral infection and their cancer. This paper discusses some of the ethical issues involved with informing head and neck cancer patients of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous research in the USA has confirmed that less than half of oncologists discuss HPV with their patients (Milbury et al, 2013) and this study showed just over half of patients were aware of their HPV diagnosis. As it is becoming more recognised that patients should be informed that HPV is the cause of their cancer (Shuman & Wolf, 2010), health professionals need to decide on the best time to discuss this with patients, with patients in this study suggesting the earlier the better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in the USA has confirmed that less than half of oncologists discuss HPV with their patients (Milbury et al, 2013) and this study showed just over half of patients were aware of their HPV diagnosis. As it is becoming more recognised that patients should be informed that HPV is the cause of their cancer (Shuman & Wolf, 2010), health professionals need to decide on the best time to discuss this with patients, with patients in this study suggesting the earlier the better.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for psychosocial distress and fear of recurrence in HNC patients is high (Badr, Gupta, Sikora, & Posner, ; Humphris & Ozakinci, ), due in part to the potential for disfigurement of the head and neck region, and dysfunction (e.g., problems with swallowing, eating) after treatment (Singer et al, ). However, identifying a sexually transmitted infection as a causal factor may lead to additional distress in patients with HPV‐oropharyngeal squamous cell carcinoma (HPV‐OSCC) and their partners (Gold, ; Longacre, Ridge, Burtness, Galloway, & Fang, ; Shuman & Wolf, ). Common patient concerns related to HPV in HNC have been documented to be how, when and why they got their cancer (Fakhry & D'Souza, ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, HPV status does not affect treatment decisions, but physicians should discuss the role of HPV, like other risk factors such as tobacco and alcohol, in the development of HNSCC in the spirit of full disclosure. (6) Yet, HPV infection is a complicated concept that requires a substantial time investment on the part of physicians for a detailed explanation that results in adequate patient comprehension. Given the gravity of a HNSCC diagnosis, questions about HPV may be overshadowed by conversations about cancer and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…20 Evidence suggests that even primary healthcare professionals involved in taking cervical smears may avoid talking to patients about HPV, 21 but head and neck clinics must make such conversations part of routine practice, 22 despite the fact that patients and clinical teams may be unused to discussing matters relating to sexual health. A systematic review identified a range of responses to HPV infection, including concerns regarding disclosure of a sexually transmitted infection, impact on relationships, and fear of stigmatization.…”
Section: The Psychological Impact Of Human Papillomavirusmentioning
confidence: 99%
“…A systematic review identified a range of responses to HPV infection, including concerns regarding disclosure of a sexually transmitted infection, impact on relationships, and fear of stigmatization. 20 Evidence suggests that even primary healthcare professionals involved in taking cervical smears may avoid talking to patients about HPV, 21 but head and neck clinics must make such conversations part of routine practice, 22 despite the fact that patients and clinical teams may be unused to discussing matters relating to sexual health. The following key messages may help address some common patient concerns.…”
Section: The Psychological Impact Of Human Papillomavirusmentioning
confidence: 99%